2015
DOI: 10.1016/j.crpv.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A retouched bone shaft from the Late Mousterian at Fumane cave (Italy). Technological, experimental and micro-wear analysis

Abstract: This paper describes a retouched bone shaft found in a Late Mousterian layer at Fumane Cave, northern Italy. The interpretation of the anthropic nature of the retouch is based on the identification of specific morpho-technological markers through experimentation. An integrated taphonomic and technological analysis was applied to the archaeological artifact. The evidence suggests that the bone shaft modifications involved the use of direct percussion through a transfer of technical knowledge from flint knapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Finally, we do not find in our experimental material the high prevalence of long bone fragments observed in the PBT sample with numerous contiguous and interspersed series of flake scars. Considering the sedimentary context, the rarity of carnivore modifications on all examined samples and the fact that experimental deliberate flaking of bone fragments of the same type and size produce flake scars comparable to those observed on the archeological specimens (ETTOS, 1985;Vincent, 1993;Romandini et al, 2015;Baumann et al, 2020), we must conclude that a subsample of PBT and RCS should be interpreted as composed by bone fragments that were deliberately modified through percussion by Lingjing hominins. The most probable goal of this behaviour was that of using the resulting retouched bone fragments as tools.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, we do not find in our experimental material the high prevalence of long bone fragments observed in the PBT sample with numerous contiguous and interspersed series of flake scars. Considering the sedimentary context, the rarity of carnivore modifications on all examined samples and the fact that experimental deliberate flaking of bone fragments of the same type and size produce flake scars comparable to those observed on the archeological specimens (ETTOS, 1985;Vincent, 1993;Romandini et al, 2015;Baumann et al, 2020), we must conclude that a subsample of PBT and RCS should be interpreted as composed by bone fragments that were deliberately modified through percussion by Lingjing hominins. The most probable goal of this behaviour was that of using the resulting retouched bone fragments as tools.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, these features are also shared with the Aurignacian bone industry from Fumane (Broglio et al 2006). At Fumane, the handful of bone tools (one awl and two fragments of worked rib) found in layer A3 (Peresani et al 2016), provide less substantial evidence of the Uluzzian worked-bone industry than is known at Grotta del Cavallo, Castelcivita, La Fabbrica and Riparo Broion. This is with the exception of the only bone scraper (Romandini et al 2014) and bone retouchers (Jéquier et al 2012) found at the site, which are artifacts commonly found in the MP-UP transitional technocomplexes. In the extensive debate surrounding the modifications in human societies that occurred in concomitance with the spread of Anatomically Modern Humans in Europe, a key role is played by the shell assemblages largely used as ornamental and symbolic objects (Vanhaeren and d'Errico 2006).…”
Section: Bone Technologymentioning
confidence: 82%
“…Finally, we do not find in our experimental material the high prevalence of long bone fragments observed in the PBT sample with numerous contiguous and interspersed series of flake scars. Considering the sedimentary context, the rarity of carnivore modifications on all examined samples and the fact that experimental deliberate flaking of bone fragments of the same type and size produce flake scars comparable to those observed on the archeological specimens [54,[157][158][159], we must conclude that a subsample of PBT and RCS should be interpreted as composed by bone fragments that were deliberately modified through percussion by Lingjing hominins. The most probable goal of this behaviour was that of using the resulting retouched bone fragments as tools.…”
Section: Plos Onementioning
confidence: 99%